Dinámica folicular en receptoras de embriones bovinos sincronizadas con un J-SYNCH modificado y normal sobre los niveles hormonales - Figueroa Párraga, María Vanessa (2019)
The objective of this investigation was to evaluate the follicular dynamics in recipients of bovine embryos synchronized with a modified and normal J-Synch on the levels of estradiol and progesterone. A procedure of general and mixed models with logit link was used to determine the influence of the different variables and their interactions with an alpha of <0.05 to determine significant differences and a value of <0.10 for significant trends. All data was analyzed with the InfoStat statistical package (Di Rienzo et al., 2019). As a result, there were significant differences in the Conventional group transferring more cows 90.0% (18:20), also statistically (P <0.05), the diameter of the luteal bodies of the J-Synch group of 7 days (21.89 ± 0.81 mm) were greater than Conventional (16.81 ± 0.95 mm). There were statistical differences (P <0.05) in the diameter of the follicle between treatments, this was greater in the group of J-Synch cows of 7 days (16.4 ± 0.2 mm). In addition, between the levels of progesterone there were significant differences for the level of progesterone at 7 days post heat, the cows of the J-Synch group were 6 days (5.03 ± 1.2 ng), while, for levels of estradiol, there were no significant differences between the groups evaluated. It is concluded that with the 7-day J-Synch treatment, a longer duration of the proestro was obtained, a greater diameter of luteal bodies and of follicles than with the Conventional treatment, which could be a viable alternative to achieve high pregnancy rates in embryo recipients.